COMMUNITY CULTURE AND ITS ROLE IN MARKETING BANKING SERVICES - AN APPLIED STUDY ON A SAMPLE OF BANKS IN THE MIDDLE EUPHRATES REGION FOR THE PERIOD AFTER 2003 - Ibrahim Rasool Hani; Muiead Abdul hussein Khaleel Alfadhel (Scholars Digest Publishing, 2025)
Many countries are distinguished by the level of services they provide to customers, whether these services are of a financial, health, tourism, or similar nature. As far as financial and banking services are concerned, certain countries have distinguished themselves in this type of service, such as Switzerland, Belgium, Britain, and others. Many researchers have addressed the issue of evaluating the levels of this service, and the focus has been on the reason for the development and flourishing of banking services in certain countries rather than others. Some of them have addressed this with some importance, especially the issue of the culture of society and the social environment that fosters this type of service.